Kualitas Layanan Elektronik DJP Online Terhadap Kepuasan Pengguna Dengan Mediasi Kepercayaan - Isebel Sara Sade Adu; Sudarwati; Ida Aryati DPW (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to determine the effect of the quality of DJP Online 's electronic services on user satisfaction with the mediation of trust. This research method uses a quantitative descriptive research design. The population of non-business individual taxpayers with active status until 2023 is 125,360 spread across 17 Kapanewon in Sleman Regency. The sample taken was 170 taxpayers using a non-probability sampling technique, purposive sampling method. Data collection using questionnaires. The data analysis technique used is SEM-PLS using SmartPLS 3.0 software. The research results show that the quality of electronic services has a positive and significant effect on trust, trust has a positive and significant effect on user satisfaction, the quality of electronic services has a positive and significant effect on user satisfaction, and the quality of electronic services has a positive and significant effect on user satisfaction through the mediation of trust. The suggestion from this research is that monitoring and evaluation of services in electronic form, in this case DJP Online, can be carried out so that improvements can be made continuously so that public trust and satisfaction with DJP services increases.